A Review of Pathway-Based Analysis Tools That Visualize Genetic Variants - Cirillo, Elisa; Parnell, Laurence D.; Evelo, Chris T. (Frontiers in Genetics, 2017)
Pathway analysis is a powerful method for data analysis in genomics, most often applied to gene expression analysis. It is also promising for SNP data analysis, such as Genome Wide Association Study (GWAS) data, because it allows the interpretation of variants with respect to the biological processes in which the affected genes and proteins are involved. Such analyses support an interactive evaluation of the possible effects of variations on function, regulation or interaction of gene products. Current pathway analysis software often does not support data visualisation of variants in pathways as an alternate method to interpret genetic association results, and specific statistical methods for pathway analysis of SNP data are not combined with these visualisation features. In this review we first describe the visualisation options of the tools that were identified by a literature review, in order to provide insight for improvements in this developing field. Tool evaluation was performed using a computational epistatic dataset of gene-gene interactions for obesity risk. Next, we report the necessity to include in these tools statistical methods designed for the pathway-based analysis with SNP data, expressly aiming to define features for more comprehensive pathway-based analysis tools. We conclude by recognizing that pathway analysis of genetic variations data requires a sophisticated combination of the most useful and informative visual aspects of the various tools evaluated.